Preschool and Pre-Primary Age Child’s Self-Assessment of His / Her Own Actions: Pedagogues’ Insights - Lažauninkienė, Sonata (Jaunųjų mokslininkų darbai, 2020)
A preschool and pre-primary age child’s self-assessment of his/her own actions is an important but insufficiently studied phenomenon. Therefore, the purpose of this work was to reveal pre-school teachers’ attitudes to a pre-school and pre-primary age child’s self-assessment of his/her own actions. 8 pre-school pedagogues from Kaunas city and Kaišiadorys district preschool education institutions were interviewed. Qualitative content analysis was performed.According to the respondents, the self-assessment process can be defined by highlighting the self-assessment concept, its objectives, skills to be developed and methods for developing those skills. They pointed out that the main objectives of selfassessment are building self-esteem, developing the ability to take responsibility for own learning and raising self-awareness in children. Self-assessment skills include four skills: assess own actions following certain rules, think about consequences, enjoy results and monitor own progress.The present qualitative study showed that various formal and informal self-assessment methods used in early childhood education can lead to success in children education. The respondents said that self-assessment boosts self-confidence, responsibility and self-awareness, builds foundation for critical and reflective thinking and enhances motivation to learn.
Keywords: preschool education; education; child; actions; self-assessment; pedagogue